2015
DOI: 10.1002/ijop.12191
|View full text |Cite
|
Sign up to set email alerts
|

I am AmeriBritSouthAfrican‐Zambian: Multidimensional remote acculturation and well‐being among urban Zambian adolescents

Abstract: One impact of globalisation is that adolescents today are frequently exposed to the values, attitudes and norms of other nations without leaving their own backyards. This may lead to remote acculturation-cultural and psychological changes experienced by non-migrant individuals having indirect and/or intermittent contact with a geographically separate culture. Using quantitative and qualitative data, we examined multidimensional remote acculturation among 83 urban Zambian adolescents who are routinely exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…However, heritage culture learning is qualitatively different from acquiring a second culture, even if both processes occur remotely. Young people's degree of remote ac culturation can be correlated with less satisfaction in life , more parent–child conflict , and poorer nutrition , likely because learning a new culture remotely can perturb cultural identity and family interactions. In contrast, remote en culturation into one's heritage culture is expected to connect an individual with family history and inform the development of core ethnic identity, both of which are positively correlated with psychological, academic, and health outcomes for youth of color .…”
Section: Remote Enculturation and Related Constructsmentioning
confidence: 99%
“…However, heritage culture learning is qualitatively different from acquiring a second culture, even if both processes occur remotely. Young people's degree of remote ac culturation can be correlated with less satisfaction in life , more parent–child conflict , and poorer nutrition , likely because learning a new culture remotely can perturb cultural identity and family interactions. In contrast, remote en culturation into one's heritage culture is expected to connect an individual with family history and inform the development of core ethnic identity, both of which are positively correlated with psychological, academic, and health outcomes for youth of color .…”
Section: Remote Enculturation and Related Constructsmentioning
confidence: 99%
“…They found that Americanisation was more prevalent in South African youth compared to Jamaican youth; notably, the exposure to American media, the relationship between Americanisation and well-being was mainly moderated by racial group membership . In another study by Ferguson and colleagues (Ferguson et al ., 2017) of 83 adolescents from Lusaka, they found that adolescents could be either classified as traditional Zambians (which meant that they were more oriented toward Zambian culture) or Westernised Multicultural Zambians (which meant that they were more oriented toward American, British, and South African contexts) . This latter group presented a lower sense of family obligation and were more independent .…”
Section: Multidimensional Model Of Acculturationmentioning
confidence: 96%
“…Even in multidimensional considerations of acculturation, outcomes of acculturation seem to be somewhat associated with Western cultural values, norms, and attitudes (Adams & Abubakar, 2016) . Remarkably, this is also the case in studies of remote acculturation (cultural changes due to indirect contact); the emphasis is on the degree to which individuals adopt Western norms, values and practices, and identify with western cultures with which they have made little or no contact but which are remotely transferred through media, social media, and/or goods and services (Ferguson & Adams, 2016;Ferguson et al ., 2017) . Identity is diffused in some African contexts .…”
Section: Reflections On Acculturation and Identity In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Partiality communicates that individuals typically adopt some, but not all, elements of a given culture and plurality acknowledges that multiple simultaneous cultural affiliations are possible and even common. According to the partiality principle, RA can be “shallow” (primarily behavioral: Ferguson & Adams, ) or “deep” (observable in identity and values: Y. L. Ferguson, K. T. Ferguson, & G. F. Ferguson, ). And according to the plurality principle, RA can be multidimensional (“Westernized multicultural Malawian” youth in Malawi were strongly oriented toward U.S., U.K., and South African cultures in addition to their own Malawian culture: K. T. Ferguson et al., ).…”
Section: Remote Acculturationmentioning
confidence: 99%